Antibacterial, Antifungal, Antioxidant, and Photoprotective Analysis of Mangrove Extracts as Additives Ingredients in a Cosmetic Cream - Putri, Dear Berliana; Pringgenies, Delianis; Trianto, Agus (Bogor Agricultural University, Indonesia, 2025)
Mangroves are a rich source of natural antioxidant compounds that can inhibit and reduce tissue damage caused by free radical activity. Currently, cosmetic creams are widely recommended for maintaining skin health and aesthetics, especially in protecting against the harmful effects of free radicals. This study applied mangrove extract as an additive ingredient in a cosmetic cream, serving as an antibacterial, antifungal, antioxidant, and photoprotective agent. Mangrove samples were collected from the mangrove ecosystem in Tapak Village, Semarang, Indonesia. Three mangrove species were evaluated for their bioactivity, and the species with the highest bioactivity was selected for use in the cream formulation. Antibacterial and antifungal activities were tested using the disc diffusion method, antioxidant activity was assessed using the DPPH method, and photoprotective activity was determined using UV spectrophotometry, with analysis based on the Mansur mathematical equation. The cream was evaluated for its characteristics, including spreadability, homogeneity, sensory properties, pH, sun protection factor (SPF), phytochemical content, stability, and microbial contamination. An in vivo was conducted to assess the cream’s effectiveness on white mice. Results indicated that Avicennia marina leaf extract exhibited the highest bioactivity compared to the other two species, Rhizophora mucronata and Bruguiera gymnorrhiza. Consequently, A. marina leaf extract was selected as the active additive ingredient in the cream formulation. Characterization tests demonstrated that the cream was stable and met standard criteria for quality. The in vivo analysis revealed that the mangrove leaf extract cream significantly prevented epidermal thinning, reduced neutrophil counts, and preserved fibroblast numbers.